EVALUATION OF THE EFFECTIVENESS OF COMPREHENSIVE TREATMENT FOR CHRONIC CATARRHAL STOMATITIS IN PATIENTS WITH GASTROINTESTINAL PATHOLOGY - Labush, Yu. Z. (Актуальні проблеми сучасної медицини Вісник Української медичної стоматологічної академії, 2025)
Relevance. Diseases of the oral mucosa are among the significant issues in therapeutic dentistry. They often develop against the background of systemic diseases, particularly gastrointestinal tract pathologies, which necessitates a rational approach to their diagnosis and treatment. Therefore, the development of comprehensive treatment and prophylaxis strategies aimed at preventing oral mucosal diseases and improving treatment effectiveness is highly relevant. Objective: To determine the effectiveness of comprehensive treatment for chronic catarrhal stomatitis in patients with chronic gastrointestinal diseases using a developed therapeutic and preventive complex. Participants and Methods. Comprehensive treatment of chronic catarrhal stomatitis was administered to 37 patients aged 20 – 44 years with concomitant gastrointestinal pathology. Of these, 20 patients were assigned to the main group and 17 to the control group. All participants received standardized etiopathogenetic therapy for the underlying gastrointestinal condition, prescribed by a gastroenterologist in accordance with established clinical protocols. Local treatment for chronic catarrhal stomatitis was identical in both groups and followed current clinical guidelines in therapeutic dentistry. In addition to standard therapy, patients in the main group received the proposed treatment regimen, which involved the application of a phytogel to the oral mucosa in doses of 0.5–1.0 g, administered 20–40 minutes before meals. To enhance the efficacy of the phytogel, patients were also prescribed “Quertulin” (600 mg) sublingual tablets: one tablet 30 minutes prior to phytogel application, a second tablet 6 hours later, and a third tablet 12 hours later, over a 10-day period. Treatment effectiveness was evaluated through clinical assessment and analysis of biochemical and immunological parameters of oral fluid. Results and discussion. The proposed local treatment measures reduced pain sensations in the patients, allowing them to improve oral hygiene practice and thus, the overall hygiene status of the oral cavity (with average scores ranging from 0.9±0.07 to 1.3±0.09 points, corresponding to a satisfactory level). Improved oral hygiene facilitated salivation and increased local oral immunity. After treatment in the main group, a statistically significant increase in sIgA levels was observed, along with a corresponding decrease in its monomeric form (mIgA) and IgG. These results indicate normalization of the humoral component of specific local immunity, attributed to the positive effects of the proposed medications. In the comparison group, only a slight trend toward improvement in immunological results was noted, indicating low treatment efficacy and a potential risk of recurrence of oral mucosal diseases. Conclusion. The developed treatment regimen for the prevention of chronic catarrhal stomatitis using pathogenetically directed local pharmacotherapy has advantages over generally accepted methods: it promotes stable remission of the disease, prevents further progression of the process, relapse of the disease, and significantly reduces the duration of treatment.